Decoding the Taboo: A Semiotic Look at Bincang Ranjang - Tito Mahesa Wijaya; Niken Hafshah Aabidah; Dick Juan Valentino; Ahmad Aqila Farid Fadilla; Muizzu Nurhadi (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines the YouTube podcast Bincang Ranjang, an Indonesian show in which guests, mostly women, openly discuss their sex lives, a topic traditionally treated as private and taboo. Using Roland Barthes' semiotic concepts of denotation/connotation, myth, and second-order signification, this research analyzes two texts: a primary episode transcript and a secondary interview with the show's host, Anisa Alatas. The findings show that the show negotiates the line between taboo and public acceptability through a consistent lexicon of euphemism, verbal purification rituals, a visual-verbal contradiction in how the host presents herself, and a moral closure that restores conventional gender norms after each story. These findings suggest that Bincang Ranjang does not eliminate the taboo surrounding sexuality in Indonesian pop culture, but rather constructs a sign system that allows taboo content and public acceptability to coexist.